Exploration of Student's Critical Thinking Skills in the Context of Chemistry Based on the Nature of Science - Suwahono Suwahono; R. Krisna Dara Alifa Zulfirman (Jurnal Tadris Kimiya, 2023)
Understanding the Nature of Science (NoS) could help improve thinking and reasoning skills. Students could use their critical thinking (CT) skills to help themselves in solving problems. Based on the NoS, this study sought to assess the CT skills of chemistry pre-service teachers at university. This study used a qualitative with a case study as the method. A purposive sampling technique was elaborated to select the research object. The respondents were chemistry students at university. The data sources were open-ended questions and interviews from the NoS questionnaire. The method of data triangulation was employed to conclude the study findings. The results showed that the CT skills possessed by chemistry pre-service teachers: were interpretation skills, inference skills, and self-regulation skills. Those skills were still in the low category. The participants also lacked in explaining, evaluating, and analyzing the students' abilities. Thus, the understanding of NoS informants can be categorized in the transitional cohort. The research findings became the department's input because some students still struggled to analyze NoS aspects in chemistry, especially through each stage of CT skills. Hence, future research is suggested to develop the students' CT skills in applying the NoS aspect in chemistry learning, especially for the pre-service teacher.